Telaah Pemikiran Abdul Daem al-Kahell Tentang Dzikir Dalam Al-Qur’an - Ali Ridho, Makhrus; Ali Ridho, Muh. Makhrus; Adi Anggara, Deki Ridho; Rahman Akbar, Ahmad Fadly; Rohmania, Nehayatul (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2024)
The era of development is racing against rationality to deal with problems and religious practices are put aside. The reality is th at even high intellectuals have not been able to properly control their emotions and spirituality. That way there is a need for training to increase spirituality in order to lead a good life. This study uses thematic interpretation with library research. From this study, according to Abdul Daem Al-Kaheel, dhikr has a connection with spiritual intelligence, this is found in the benefits of dhikr which gives peace of mind. And dhikr has a good impact on one of the members of the human body, namely the brain, where there is a very clear influence on brain signal emission when doing dhikr. At the end of the study, the writer realizes that this research is not perfect and certainly requires more in-depth analysis, regarding dhikr which is closely related to human life. so the researchers hope that there will be an in-depth study of dzikr that can be applied to humans in order to lead a more meaningful life.